Differential use of vertical space by small mammals in the Monte Desert, Argentina - Albanese, María Soledad (2011)
Space use in deserts usually has been considered only along the horizontal dimension; however, vertical structure could be an important variable for habitat segregation among small mammal species. Our study assessed the use of vertical space by small mammals of the Monte Desert by live-trapping animals at different heights. We recorded 1,336 captures of 4 rodent and 1 marsupial species in 27,600 trap nights. All 5 species were captured on the ground and in tree layers, but only the gray leaf-eared mouse (Graomys griseoflavus) and the desert mouse opossum (Thylamys pallidior) used vertical space appreciably. G. griseoflavus used the arboreal space independently of habitat, plant species, or branch diameter, whereas T. pallidior showed a more selective behavior, being present at greater heights and on large-diameter branches of Prosopis trees. All rodent species used lower more than higher parts of arboreal strata. They used vertical space more or only during the dry season when resource availability is low. Our study suggests that vertical structure offers greater opportunities to acquire resources when these are scarce and plays a role in the coexistence of small desert mammals.